The Legacy of Zellig Harris : language and information into the 21st century. - Nevin, Bruce E.; Johnson, Stephen M. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2002)
Zellig Harris opened many lines of research in language, information, and culture, from generative grammar to informatics, from mathematics to language pedagogy. An international array of scholars here describe further developments and relate this work to that of others. Volume 1 begins with a survey article by Harris himself, previously unavailable in English. T.A. Ryckman, Paul Mattick, Maurice Gross, and Francis Lin show the importance of Harris's methodology for philosophy of science, the first two with reference especially to his remarkable findings on the form of information in science.